ANALISIS MINAT MAHASISWA MEMBUKA TABUNGAN EMAS DI BANK SYARIAH INDONESIA (STUDI PADA MAHASISWA FEBI UIN STS JAMBI) - Sri Hartatik; Usdeldi Usdeldi; Nova Erliyana (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
Gold is an investment that is in great demand by the people of Indonesia. However, in this study it was found that there were no students who had opened gold savings for investment in Bank Syariah Indonesia, but there were those who had opened other investments in stocks and Pawnshops. To find out the interest of students in opening gold savings, the obstacles and the right solutions to deal with this. In this study using a qualitative approach method which was carried out on 20 informants to find answers to existing problems. Of the 20 informants in the study, 95% of them agreed with the indicators in this study and 5% of the informants disagreed with the indicators in this study.